Polluted River Problems and Games with a Permission Structure - René van den Brink; Simin He; Jia-Ping Huang (Tinbergen Institute, 2015)
Polluted rivers are harmful to human, animals and plants living along it. To reduce the harm, cleaning costs are generated. However, when the river passes through several different countries or regions, a relevant question is how should the costs be shared among the agents. Ni and Wang (2007) first consider this problem as cost sharing problems on a river network, shortly called polluted river problems. They consider rivers with one spring which was generalized by Dong, Ni, and Wang (2012) to rivers with multiple springs. They introduce and axiomatize three cost sharing methods: the Local Responsibility Sharing (LRS) method, the Upstream Equal Sharing (UES) method and the Downstream Equal Sharing (DES) method. In this paper, we show that the UES and DES methods can also be obtained as the conjunctive permission value of an associated game with a permission structure, where the permission structure corresponds to the river structure and the game is determined by the cleaning costs. Then, we show that several axiomatizations of the conjunctive permission value also give axiomatizations of the UES and DES methods, of which one is comparable with the one from Dong, Ni, and Wang (2012). Besides, by applying another solution, the disjunctive permission value, to polluted river games with a permission structure we obtain a new cost allocation method for polluted river problems. We axiomatize this solution and compare it with the UES method.
Keywords: C71; D61; D62; 330; Polluted river; cost sharing; axiomatization; permission values